Safety and efficacy of transcatheter edge-to-edge repair (TEER) in patients with history of cancer. (February 2023) - Khan, Sahoor; Dani, Sourbha S.; Hermann, Joerg; Neilan, Tomas.G.; Lenihan, Daniel J.; Fradley, Michael; Parikh, Rohan; Khan, Saafi; Deswal, Anita; Liu, Jennifer; Barac, Ana; Labib, Sherif; et al.
Abstract: Background: Surgical therapy has been a long-standing option for valvular heart disease, in patients with history of cancer, it carries an increased risk of complications. Objectives: Transcatheter edge-to-edge repair (TEER) for mitral regurgitation, represents a less invasive option. However, patients with history of cancer have generally been excluded from trials. Methods: A retrospective cohort analysis was performed on de-identified, aggregate patient data from the TriNetX research network. Patients 18 ≥ years of age, who had undergone TEER between January 1, 2013 and May 19, 2021, were identified using the CPT codes and divided into two cohorts based on a history of cancer. Subgroup analysis was performed based on history of systemic antineoplastic therapy. Odds ratio and log-rank test were used to compare the outcomes over 1 and 12-months. Results: In matched cohorts (503 patients in each, mean age 77.7 years, men 55 vs 58 %, white 84 vs 87 % in non-cancer and cancer cohorts respectively), the risk of heart failure exacerbation, all-cause mortality and all-cause hospitalizations were similar at 1 and 12 months among patients undergoing TEER. Risk of major complications (ischemic stroke, blood product transfusion and cardiac tamponade) were also similar. In the cancer cohort, hematologic/lymphoid malignancies were the most common (28.0 %) and 12.5 % patients had a history of metastatic cancer. There was no significant difference in heart failure exacerbation or all-cause mortality based on history of systemic antineoplastic therapy. Conclusions: Overall outcomes following TEER are similar in patients with a history of cancer and should be considered in selected patients in this population.